Moral Injury as Mediating Variable between Client Pressure and Auditor Professional Judgment - Masculine Muhammad Muqorobin; Affix Mareta; Beta Estri Adiana; Ahmad Abdul Aziz; Alex Johanes Simamora (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2026)
This study aims to examine the effect of client pressure on auditors’ professional judgment with moral injury as a mediating variable. The study uses a quantitative approach through a questionnaire survey distributed to 256 auditors working in Indonesian public accounting firms. The data are analyzed using Structural Equation Modeling (SEM) to test the relationships among variables. The results show that client pressure has a positive effect on auditors’ moral injury. Furthermore, moral injury has a negative effect on auditors’ professional judgment. The findings also indicate that moral injury mediates the relationship between client pressure and professional judgment, suggesting that the impact of client pressure on audit decisions operates not only directly but also through auditors’ internal psychological mechanisms. This research introduces the concept of moral injury into the auditing context as a psychological mechanism explaining how client pressure can undermine the quality of auditors' professional judgment.